2013
DOI: 10.3389/fnhum.2013.00905
|View full text |Cite
|
Sign up to set email alerts
|

The neural coding of creative idea generation across adolescence and early adulthood

Abstract: Creativity is considered key to human prosperity, yet the neurocognitive principles underlying creative performance, and their development, are still poorly understood. To fill this void, we examined the neural correlates of divergent thinking in adults (25–30 years) and adolescents (15–17 years). Participants generated alternative uses (AU) or ordinary characteristics (OC) for common objects while brain activity was assessed using fMRI. Adults outperformed adolescents on the number of solutions for AU and OC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
92
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(108 citation statements)
references
References 83 publications
(120 reference statements)
16
92
0
Order By: Relevance
“…The Main effect AU>OC during the alternative uses task in the scanner (AUT-scanner) at pre-test (n = 32) provided a replication of earlier findings [10].…”
Section: Resultssupporting
confidence: 71%
“…The Main effect AU>OC during the alternative uses task in the scanner (AUT-scanner) at pre-test (n = 32) provided a replication of earlier findings [10].…”
Section: Resultssupporting
confidence: 71%
“…Furthermore, the degree of flexibility in thinking requires a variety of strategies to creatively approach a given clinical problem, and, as such, requires a tolerance for ambiguity and a reflective understanding of the practice, both during the clinical-reasoning process (reflection in action) and retrospectively (reflection on action). Recent neuroimaging evidence suggests that creative behavior and generation of spontaneous and novel ideas require activation of self-monitoring regions of the medial frontal cortex and a subsequent deactivation of cognitive control regions, such as the lateral frontal cortex (Limb & Braun 2008;Liu et al 2012;Takeuchi et al 2012;Kleibeuker et al 2013;Wiggins & Bhattacharya 2014). Therefore, we would expect deactivation in the lateral frontal regions and activation in the medial frontal regions during analytic reasoning with respect to self-reported flexibility of thinking, consistent with the brain processes reported during spontaneous/creative behavior.…”
Section: Practice Pointssupporting
confidence: 67%
“…Notably, this degree of brain maturation plays a critical role in cognitive development and has different age-related activation (Bunge and Wright, 2007). A recent study also reported that the left lateral PFC was more activated in adults than in adolescents during performing divergent thinking task (Kleibeuker et al, 2013). Although age range of this sample appears to be larger across the adolescence and adult-age of most subjects is between 18 and 21 years-it may bring about unbiased results to discuss particular regions that mature late after adolescence.…”
Section: Variations In Structure and Function Contribute To Verbal Crmentioning
confidence: 97%